Factors Affecting the Implementation of Clinical Pharmacy Services in China. (March 2014) - Penm, Jonathan; Moles, Rebekah; Wang, Holly; Li, Yan; Chaar, Betty
New policies in China have recently led to the implementation of clinical pharmacy services in hospitals. We explored the views of hospital administrators, pharmacy directors, clinical pharmacists, and dispensing pharmacists about the factors affecting clinical pharmacy services in China, using the framework approach and organizational theory. We conducted 30 interviews with 130 participants at 29 hospitals (both secondary and tertiary) in Beijing, Zhengzhou, Luoyang, and Shanghai. We found that the barriers to and facilitators of implementation of clinical pharmacy services slotted into the environment and participant dimensions of Scott's adapted version of Leavitt's organizational model. External support from government was perceived as crucial to promoting pharmacy services. It is proposed that the internationally recognized Basel Statements of the International Pharmaceutical Federation also provide a strong foundation for guiding China in implementing clinical pharmacy services.